MENELISIK AUTENTISITAS SEBUAH HADIS: STUDI ATAS KAIDAH KESHAHIHAN HADIS DITILIK DARI SANAD DAN MATAN - Suhaimi, Syukron Mahbub (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2021)
Abstract It is considered very urgent to seek the authenticity of a hadith for academics and practitioners of Islamic law so that they should easily be able to identify the authenticity of the hadith. So that it can be used as an objective reference basis in writing and berhujjah for those who are concerned in the field of hadith. A hadith can be declared as a valid hadith if it has five criteria, namely: (1) the sanad is continuous, (2) it is narrated by a just person, (3) it is narrated by a dabit person, (4) there are no irregularities in the hadith, and (5) the absence of 'illat. These five criteria are included in the sanad and matan of the hadith which will be explained in detail later. The method in compiling this article is done by reviewing the literature related to the rules of hadith validity which is then carried out as a kind of study both objectively and subjectively. Keywords: Sahih Hadith, Sanad, Matan.